Aluminum alloy material for current-carrying friction pair and preparation method of aluminum alloy material

By using aluminum alloy materials containing Cu, Sc, and Zr in the current-carrying friction pair material, and forming heat-resistant reinforced phases and refining grains through heat treatment, the existing materials have been solved, and a high-performance current-carrying friction pair material is achieved.

CN119685668APending Publication Date: 2025-03-25SOUTHWEST JIAOTONG UNIV
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411861927.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-17
Publication Date
2025-03-25

AI Technical Summary

Technical Problem

The existing current-carrying friction pair materials have high density, high wear rate, low strength and low flow quality, which cannot meet the development needs of high-speed trains.

Method used

An aluminum alloy material is used, containing 5-10% Cu, 0-0.3% Sc, 0.2-0.6% Zr, and the balance is Al and inevitable impurities. The heat-resistant Al2Cu reinforced phase is formed by adding an appropriate amount of Cu element and heat treatment. The grains are refined and grain boundary dispersion is increased to reduce the adverse effects of Cu element on electrical conductivity.

Benefits of technology

This aluminum alloy material has high specific strength, hardness and conductivity after heat treatment, and has excellent current-carrying wear resistance. It can effectively reduce the density and wear rate of friction discs, improve current-carrying quality, and meet the material needs of high-speed trains.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119685668A_ABST
    Figure CN119685668A_ABST
Patent Text Reader

Abstract

The invention discloses an aluminum alloy material for a current-carrying friction pair and a preparation method of the aluminum alloy material, and belongs to the technical field of alloy materials. The aluminum alloy provided by the invention comprises the following components in percentage by weight: 5-10% of Cu, 0-0.3% of Sc, 0.2-0.6% of Zr and the balance of Al and inevitable impurities. The preparation method comprises the following steps: S1, weighing raw materials, and pretreating for later use; s2, raw materials are smelted and degassed, and alloy melt is obtained; s3, the alloy melt is poured into a die casting machine for die casting; and S4, the die casting is sequentially subjected to solution treatment and aging treatment and then is air-cooled to the room temperature, and the die casting is obtained. The prepared aluminum alloy material has the beneficial effects of being good in casting performance, high in specific strength, hardness, conductivity and current-carrying wear resistance and the like, and the requirement for serving as a current-carrying friction pair material of a high-speed train is met.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of alloy materials, and in particular relates to an aluminum alloy material for a current-carrying friction pair and a preparation method thereof. Background Art

[0002] Against the background of the rapid development of my country's rail high-speed trains, the demand for lightweight, low-cost and long-life current-carrying friction pair materials for high-speed trains is increasing. The service environment of current-carrying friction pairs is becoming increasingly harsh, and the damage and failure behavior is becoming more and more complex. The service performance requirements of current-carrying friction pair materials are constantly increasing, requiring the materials to have comprehensive properties such as high strength, high conductivity, high wear resistance, electrical corrosion resistance and high temperature softening resistance.

[0003] At present, the research on current-carrying friction pair materials mainly focuses on copper-based materials with excellent conductivity or graphite-based materials with good lubricity and their composite materials, but both have certain disadvantages. Copper-based materials have high density, low specific strength and high cost; graphite-based materials have high wear and low life, which cannot meet the development needs of high-speed trains. At the same time, the friction disc of the current-carrying friction pair has a relatively complex shape and is formed by casting. However, traditional gravity casting is prone to casting defects such as shrinkage, segregation and coarse second phase, which will seriously affect its wear resistance and conductivity, causing the current-carrying quality to decrease.

[0004] In view of the shortcomings of the current-carrying friction pair materials currently used, such as high cost, high density, low strength, large wear rate at high speed and low current-receiving quality, there is an urgent need to develop a new friction pair material that is lightweight and has excellent current-carrying wear performance. Summary of the invention

[0005] In view of the deficiencies in the prior art, the purpose of the present invention is to provide an aluminum alloy material for a current-carrying friction pair and a preparation method thereof, so as to solve the problems of high density, high wear rate, low strength and low current-receiving quality of the current-carrying friction pair material in the prior art.

[0006] The technical solution of the present invention to solve the above technical problems is as follows: an aluminum alloy material for current-carrying friction pairs comprises the following components by weight percentage: 5-10% Cu, 0-0.3% Sc, 0.2-0.6% Zr, and the remainder is Al and inevitable impurities.

[0007] The beneficial effects of the present invention are as follows: the addition of an appropriate amount of Cu element and appropriate heat treatment are conducive to the formation of an appropriate amount of heat-resistant Al2Cu strengthening phase, so that the wear resistance and electrical conductivity of the material are maintained at a high level at the same time, thereby ensuring the current-carrying wear resistance; on the other hand, there is a certain eutectic phase during casting, so that the material has good casting performance. Sc and Zr elements refine the grains, increase the grain boundary dispersed Al2Cu eutectic phase, and reduce the solid solubility of Cu elements, thereby reducing its adverse effects on the electrical conductivity of aluminum alloy materials. At the same time, the precipitation of the second phase containing Sc and Zr after heat treatment is also conducive to further improving the material's wear resistance, heat resistance and arc erosion resistance. The combined use of the two can improve the conductivity and wear resistance of the material and has higher economic efficiency.

[0008] On the basis of the above technical solution, the present invention can also be improved as follows: the following components are included in weight percentage: 5-10% Cu, 0.1-0.25% Sc, 0.3-0.5% Zr, and the balance is Al and inevitable impurities.

[0009] The present invention also provides a method for preparing the aluminum alloy material for the current-carrying friction pair, comprising the following steps:

[0010] S1. Pretreatment: According to the weight percentage of each element in the aluminum alloy material, the raw materials are prepared according to the alloy composition and the amount of burn-off, and the raw materials are pretreated for use; the weight percentage of each element is 5-10% Cu, 0-0.3% Sc, 0.2-0.6% Zr, and the balance is Al and unavoidable impurities;

[0011] S2. Alloy smelting: heating the aluminum raw material to melt, then adding the Cu raw material, the Sc raw material and the Zr raw material to the molten aluminum liquid, stirring for 10 to 20 minutes, and then passing an inert gas into the molten metal liquid for degassing for 5 to 20 minutes to obtain an alloy melt;

[0012] S3. Die casting: The alloy melt temperature is adjusted to 620-650°C, poured into a die casting machine for die casting, the mold is preheated in advance, the injection speed is 0.3-0.5 m / s, the injection pressure is 100-120 MPa, and after the injection is completed, the pressure is maintained for 3-10 seconds to obtain a die casting;

[0013] S4. Heat treatment: The die casting is subjected to solution treatment and aging treatment in sequence, and then air-cooled to room temperature.

[0014] The beneficial effects of the present invention are as follows: die casting in the semi-solid temperature range can effectively solve alloy shrinkage, segregation and coarse second phase casting defects due to its higher pressure and faster cooling rate during molding, and provide a structural basis for improving its wear resistance and electrical conductivity and improving current carrying quality.

[0015] On the basis of the above technical solution, the present invention can also be improved as follows:

[0016] Furthermore, the pretreatment in step S1 is to remove impurities and oil stains on the surfaces of the aluminum raw material and the copper raw material and dry them for standby use.

[0017] Furthermore, the aluminum raw material is pure aluminum, the Cu raw material is T2 copper, the Sc raw material is Al-Sc master alloy, and the Zr raw material is Al-Zr master alloy.

[0018] Furthermore, the solution treatment parameters are 538°C×21h, and the aging treatment parameters are 175°C×4.5h or 195°C×3h.

[0019] The beneficial effects of the above technical solution are as follows: the aluminum alloy is subjected to solid solution treatment, which can dissolve the Al2Cu phase in the cast state, and after T6 aging treatment, nano-scale precipitation phases are formed and evenly distributed in the entire alloy, thereby improving the tensile strength. After homogenization and solid solution treatment, Cu atoms form a supersaturated solid solution in the α-Al matrix. During aging treatment, the supersaturated Cu atoms combine with Al atoms to form fine precipitation phases, which are evenly distributed in the matrix. When dislocations pass through, they will do additional work and thus improve the strength of the alloy.

[0020] Furthermore, in step S2, alloy smelting is carried out in an industrial resistance furnace at a heating temperature of 820°C.

[0021] Furthermore, the inert gas is argon.

[0022] Furthermore, the mold preheating temperature is 200°C.

[0023] Furthermore, in step S3, the injection speed in the die-casting is 0.4 m / s, the injection pressure is 106 MPa, and after the injection is completed, the pressure is maintained for 5 seconds.

[0024] The present invention has the following beneficial effects:

[0025] 1. The aluminum alloy material prepared by the present invention has good casting performance, high specific strength, hardness and electrical conductivity, and good resistance to current-carrying wear, meeting the requirements for being used as a current-carrying friction pair material for high-speed trains.

[0026] 2. The aluminum alloy provided by the present invention has different friction and wear properties under different currents and sliding speeds depending on its Cu content and different preparation methods. It can be flexibly selected according to the performance requirements of the current-carrying friction pair under different working conditions to meet the requirements as a current-carrying friction pair material for high-speed trains.

[0027] 3. Compared with aluminum alloy materials prepared by other preparation processes, the alloy material of the present invention has a dense structure and a small amount of coarse second phase.

[0028] 4. Currently, the material of the current-carrying friction pair is mainly copper-based material. The aluminum-based alloy material provided by the present invention has a greatly improved lightweight level compared with copper-based materials. At the same time, it has excellent tribological properties and is cheaper. In fields that require lightweighting or cost reduction, it has more application prospects than copper-based materials. BRIEF DESCRIPTION OF THE DRAWINGS

[0029] Figure 1 This is the microstructure diagram of the aluminum alloy prepared in Example 1;

[0030] Figure 2 The wear rate variation curve of the aluminum alloy prepared in Comparative Examples 1-5 under different currents;

[0031] Figure 3 The wear rate variation curve of the aluminum alloy prepared in Examples 1-4 under different currents;

[0032] Figure 4 The wear rate variation curves of the aluminum alloys prepared in Examples 5-6 and Comparative Examples 6-7 under different currents;

[0033] Figure 5 The friction coefficient variation curve of the aluminum alloy prepared in Examples 1-6 at different sliding speeds. DETAILED DESCRIPTION

[0034] The principles and features of the present invention are described below in conjunction with the examples, which are only used to explain the present invention and are not intended to limit the scope of the present invention. If no specific conditions are specified in the examples, the conditions are carried out according to conventional conditions or the conditions recommended by the manufacturer. If the manufacturer of the reagents or instruments is not specified, they are all conventional products that can be purchased commercially.

[0035] Embodiment 1:

[0036] An aluminum alloy material (T6-Al-5Cu-Sc-Zr) for current-carrying friction pairs comprises the following components in weight percentage: 5% Cu, 0.1% Sc, 0.3% Zr, and the balance is Al and inevitable impurities.

[0037] The preparation method of the above aluminum alloy material (T6-Al-5Cu-Sc-Zr) comprises the following steps:

[0038] S1. Pretreatment: Weigh the formula amount of industrial pure aluminum ingot, T2 copper, Al-Sc master alloy, and Al-Zr master alloy, remove surface impurities and oil stains and dry them for later use;

[0039] S2. Alloy smelting: an aluminum ingot was added to an industrial resistance furnace and heated to 820°C until it was melted. T2 copper, Al-Sc master alloy, and Al-Zr master alloy were added to the molten aluminum liquid and manually stirred for 15 minutes. Then, argon gas (99.99%) was introduced into the molten metal liquid for degassing for 10 minutes to obtain an alloy melt.

[0040] S3. Die casting: The alloy melt temperature was adjusted to 650°C and poured into the steel mold cavity of a horizontal cold chamber die casting machine (DCC-280) for die casting. The injection speed was 0.4m / s, the injection pressure was 106MPa, and the mold preheating temperature was 200°C. After the injection was completed, the pressure was maintained for 5s to obtain a die casting.

[0041] S4. Heat treatment: The die casting is subjected to solution treatment and aging treatment (T6) in sequence, with the solution treatment parameters being 538°C × 21h and the aging treatment parameters being 175°C × 4.5h, and then air-cooled to room temperature.

[0042] Embodiment 2:

[0043] An aluminum alloy material (T6-Al-10Cu-Sc-Zr) for current-carrying friction pairs comprises the following components in weight percentage: 10% Cu, 0.25% Sc, 0.4% Zr, and the balance is Al and inevitable impurities.

[0044] The preparation method of the above aluminum alloy material (T6-Al-10Cu-Sc-Zr) comprises the following steps:

[0045] S1. Pretreatment: Weigh the formula amount of industrial pure aluminum ingot and T2 copper, remove surface impurities and oil stains and dry them for later use;

[0046] S2. Alloy smelting: an aluminum ingot was added to an industrial resistance furnace and heated to 820°C until it was melted. T2 copper, Al-Sc master alloy, and Al-Zr master alloy were added to the molten aluminum liquid and manually stirred for 15 minutes. Then, argon gas (99.99%) was introduced into the molten metal liquid for degassing for 10 minutes to obtain an alloy melt.

[0047] S3. Die casting: The alloy melt temperature was adjusted to 630°C and poured into the steel mold cavity of a horizontal cold chamber die casting machine (DCC-280) for die casting. The injection speed was 0.4 m / s, the injection pressure was 106 MPa, and the mold preheating temperature was 200°C. After the injection was completed, the pressure was maintained for 5 seconds to obtain a die casting.

[0048] S4. Heat treatment: The die casting is subjected to solution treatment and aging treatment (T6) in sequence, with the solution treatment parameters being 538°C × 21h and the aging treatment parameters being 175°C × 4.5h, and then air-cooled to room temperature.

[0049] Embodiment 3:

[0050] An aluminum alloy material (T7-Al-5Cu-Sc-Zr) for current-carrying friction pairs comprises the following components in weight percentage: 5% Cu, 0.1% Sc, 0.3% Zr, and the remainder is Al and inevitable impurities.

[0051] The preparation method of the above aluminum alloy material (T7-Al-5Cu-Sc-Zr) comprises the following steps:

[0052] S1. Pretreatment: Weigh the formula amount of industrial pure aluminum ingots and T2 copper, Al-Sc master alloy, and Al-Zr master alloy, remove surface impurities and oil stains and dry them for later use;

[0053] S2. Alloy smelting: an aluminum ingot was added to an industrial resistance furnace and heated to 820°C until it was melted. T2 copper, Al-Sc master alloy, and Al-Zr master alloy were added to the molten aluminum liquid and manually stirred for 15 minutes. Then, argon gas (99.99%) was introduced into the molten metal liquid for degassing for 10 minutes to obtain an alloy melt.

[0054] S3. Die casting: The alloy melt temperature was adjusted to 650°C and poured into the steel mold cavity of a horizontal cold chamber die casting machine (DCC-280) for die casting. The injection speed was 0.4m / s, the injection pressure was 106MPa, and the mold preheating temperature was 200°C. After the injection was completed, the pressure was maintained for 5s to obtain a die casting.

[0055] S4. Heat treatment: The die casting is subjected to solution treatment and aging treatment (T7) in sequence, with the solution treatment parameters being 538°C × 21h and the aging treatment parameters being 195°C × 3h, and then air-cooled to room temperature.

[0056] Embodiment 4:

[0057] An aluminum alloy material (T7-Al-10Cu-Sc-Zr) for current-carrying friction pairs comprises the following components in weight percentage: 10% Cu, 0.25% Sc, 0.4% Zr, and the balance is Al and inevitable impurities.

[0058] The preparation method of the above aluminum alloy material (T7-Al-10Cu-Sc-Zr) comprises the following steps:

[0059] S1. Pretreatment: Weigh the formula amount of industrial pure aluminum ingots and T2 copper, Al-Sc master alloy, and Al-Zr master alloy, remove surface impurities and oil stains and dry them for later use;

[0060] S2. Alloy smelting: an aluminum ingot was added to an industrial resistance furnace and heated to 820°C until it was melted. T2 copper, Al-Sc master alloy, and Al-Zr master alloy were added to the molten aluminum liquid and manually stirred for 15 minutes. Then, argon gas (99.99%) was introduced into the molten metal liquid for degassing for 10 minutes to obtain an alloy melt.

[0061] S3. Die casting: The alloy melt temperature was adjusted to 640°C and poured into the steel mold cavity of a horizontal cold chamber die casting machine (DCC-280) for die casting. The injection speed was 0.4 m / s, the injection pressure was 106 MPa, and the mold preheating temperature was 200°C. After the injection was completed, the pressure was maintained for 5 seconds to obtain a die casting.

[0062] S4. Heat treatment: The die casting is subjected to solution treatment and aging treatment (T7) in sequence, with the solution treatment parameters being 538°C × 21h and the aging treatment parameters being 195°C × 3h, and then air-cooled to room temperature.

[0063] Embodiment 5:

[0064] An aluminum alloy material (T6-Al-5Cu-Zr) for current-carrying friction pairs comprises the following components in weight percentage: 5% Cu, 0.3% Zr, and the remainder Al and inevitable impurities.

[0065] The preparation method of the above aluminum alloy material (T6-Al-5Cu-Zr) is the same as that in Example 1.

[0066] Embodiment 6:

[0067] An aluminum alloy material (T7-Al-10Cu-Zr) for current-carrying friction pairs comprises the following components in weight percentage: 5% Cu, 0.4% Zr, and the remainder Al and inevitable impurities.

[0068] The preparation method of the above aluminum alloy material (T7-Al-10Cu-Zr) is the same as that of Example 4.

[0069] Comparative Example 1:

[0070] An aluminum alloy material (Al-5Cu-Sc-Zr) for current-carrying friction pairs comprises the following components in weight percentage: 5% Cu, 0.1% Sc, 0.3% Zr, and the remainder is Al and inevitable impurities.

[0071] The difference between the preparation method of the above aluminum alloy material (Al-5Cu-Sc-Zr) and that of Example 1 is that the heat treatment in step S4 is omitted.

[0072] Comparative Example 2:

[0073] An aluminum alloy material (Al-10Cu-Sc-Zr) for current-carrying friction pairs comprises the following components in weight percentage: 10% Cu, 0.25% Sc, 0.4% Zr, and the balance is Al and inevitable impurities.

[0074] The difference between the preparation method of the above aluminum alloy material (Al-10Cu-Sc-Zr) and that of Example 2 is that the heat treatment in step S4 is omitted.

[0075] Comparative Example 3:

[0076] An aluminum alloy material (Al-15Cu-Sc-Zr) for current-carrying friction pairs comprises the following components in weight percentage: 15% Cu, 0.1% Sc, 0.3% Zr, and the balance is Al and inevitable impurities.

[0077] The difference between the preparation method of the above aluminum alloy material (Al-15Cu-Sc-Zr) and that of Example 2 is that the heat treatment in step S4 is omitted.

[0078] Comparative Example 4:

[0079] An aluminum alloy material (T6+Al-15Cu-Sc-Zr) for current-carrying friction pairs comprises the following components in weight percentage: 15% Cu, 0.1% Sc, 0.3% Zr, and the remainder is Al and inevitable impurities.

[0080] The preparation method of the above aluminum alloy material (T6+Al-15Cu-Sc-Zr) is the same as that in Example 1.

[0081] Comparative Example 5:

[0082] An aluminum alloy material (150°C / 2h-Al-5Cu-Sc-Zr) for current-carrying friction pairs comprises the following components in weight percentage: 5% Cu, 0.1% Sc, 0.3% Zr, and the remainder is Al and inevitable impurities.

[0083] The preparation method of the above aluminum alloy material (150°C / 2h-Al-5Cu-Sc-Zr) is different from that of Example 1 in that the solution treatment parameters are 538°C×21h, and the aging treatment parameters are 150°C×2h.

[0084] Comparative Example 6:

[0085] An aluminum alloy material (T6+Al-5Cu) for current-carrying friction pairs comprises the following components in terms of weight percentage: 5% Cu, and the balance Al and inevitable impurities.

[0086] The preparation method of the above aluminum alloy material (T6+Al-5Cu) is the same as that in Example 1.

[0087] Comparative Example 7:

[0088] An aluminum alloy material (T7+Al-10Cu) for current-carrying friction pairs comprises the following components in weight percentage: 10% Cu, and the balance Al and inevitable impurities.

[0089] The preparation method of the above aluminum alloy material (T7+Al-10Cu) is the same as that of Example 4.

[0090] Experimental example:

[0091] In order to test the basic properties and current-carrying wear performance of the alloy material, the alloy materials prepared in Examples 1-4 and Comparative Examples 1-4 were processed into disc-shaped specimens of Φ60mm×4mm by wire cutting, and the surfaces were polished with 400*~1200* sandpaper and polished with diamond polishing paste with a particle size of 1.5μm. They were used as basic performance test and current-carrying wear test samples, and the specific experimental results are as follows.

[0092] 1. Characterization of alloy material structure and basic properties

[0093] 1.1 Phase testing and microstructure analysis of alloy material samples

[0094] In the unheat-treated cast aluminum alloys of Comparative Examples 1-3, the eutectic structure is mainly distributed in the form of particles and discontinuous chains at the α-Al grain boundaries. As the Cu content in the alloy increases, the eutectic structure content increases, the continuous α-Al matrix is ​​divided by the eutectic structure, and the eutectic structure changes from discontinuous particles and chains to a network. In the aluminum alloy with a Cu content of 15%, even a larger block eutectic structure appears. The second phase in the eutectic structure of the alloy with a lower Cu content is mainly blocky θ(Al2Cu). As the Cu content increases, the eutectic structure gradually shows a layered structure of alternating black α-Al phases and white θ(Al2Cu) phases.

[0095] After the aluminum alloy materials of Examples 1-4 are subjected to T6 and T7 heat treatments, the long high-temperature homogenization stage will cause significant changes in the eutectic structure morphology and distribution in the original cast alloy, such as Figure 1 As shown, after the aluminum alloy of Example 1 is heat treated, the strip structure of the eutectic θ(Al2Cu) in the cast state disappears, and the strip θ(Al2Cu) is transformed into particles at high temperature, and the Cu dissolved in the matrix is ​​transformed into a fine precipitate phase and precipitates in the crystal. Sc and Zr in the aluminum alloy also generate a dispersion strengthening phase Al3(Sc,Zr), which can effectively hinder dislocation slip and grain boundary migration and θ phase coarsening, improve the wear resistance of the material, and enable the aluminum alloy to maintain stable mechanical properties under current-carrying friction conditions.

[0096] 1.2 The hardness, density and conductivity of the alloy material samples were tested, and the results are shown in Table 1:

[0097] Table 1 Basic performance parameters of alloys in various examples

[0098]

[0099]

[0100] From the data in Table 1, it can be seen that after heat treatment, the hardness of the aluminum alloy material increases significantly, and the T6 peak aging increase is the most obvious. Under T6 heat treatment, the hardness and tensile strength of the cast aluminum alloy with a Cu content of 5% increase from 58HB to 120HB, an increase of 106%; when the Cu content increases from 5% to 15%, the density of the aluminum alloy increases from 2.7g / cm 3 Increased to 3.1g / cm 3 , the conductivity decreased from 46.7% IACS to 38.1% IACS.

[0101] 2. Current-carrying wear test and morphology analysis

[0102] The current-carrying wear test samples were subjected to current-carrying wear tests at different currents and sliding speeds. The current-carrying wear pair material is the Cu / C brush currently used in high-speed trains, which is made of copper powder and graphite by powder metallurgy pressing. The main structure is a mesh Cu skeleton and intermediate coated graphite. The volume ratio of Cu to graphite is about 3:2, the hardness is 15HB, the conductivity is 6.1%IACS, the size is 34×10×10mm, and the contact area is 3.4cm 2 In order to avoid poor contact between the alloy disc and the brush, the alloy disc needs to be moderately polished before wear. After polishing, the surface roughness of the alloy disc is about Ra = 1μm. The specific parameters of the current wear test with different currents and different sliding speeds are shown in Table 2, where the sliding speed is set to 60r / s based on the fastest rotation angular velocity of the wheels of the current 350km / h EMU.

[0103] Table 2 Wear parameters under different conditions

[0104]

[0105] The wear properties of the alloy material samples prepared in Examples 1-5 and Comparative Examples 1-7 were analyzed, and the results are as follows:

[0106] 2.1 Analysis of current-carrying wear performance of aluminum alloy materials under different currents

[0107] Figure 2The wear rate variation curve of the aluminum alloys prepared in Comparative Examples 1-5 under different currents can be seen from the figure that with the increase of current, the wear rate of the cast aluminum alloys prepared in Comparative Examples 1-3 shows a trend of first decreasing and then increasing. Under the condition of non-current carrying current of 0A, the alloy has a high wear rate due to the limited formation of the oxide mixed layer on the alloy surface, severe matrix tearing and peeling. The intervention of current promotes graphite transfer and oxidation of the worn surface to form an oxide mixed layer, which plays a lubricating and protective role and significantly reduces the wear rate compared to the non-current carrying condition. As the current continues to increase, the wear temperature continues to increase, adhesive wear and arc erosion intensify, and the wear rate continues to increase. Under a current of 180A, the aluminum alloy material with 5% Cu content has the lowest wear rate, which is 1.9×10 -5 mm 3 N -1 m -1 .

[0108] Figure 3 The wear rate curves of the aluminum alloys after heat treatment of Examples 1-4 under different currents show that as the current increases, the difference between the oxidation mixed layer of the aluminum alloys after heat treatment and under current conditions still exists, and the wear rate shows a trend of first decreasing and then increasing. Compared with the cast state, the wear rate and wear temperature are reduced; under high current, the wear performance of the alloy in the T6 state is better than that of the T7.

[0109] Figure 4 The wear rate variation curves of the aluminum alloys prepared in Examples 5-6 and Comparative Examples 6-7 under different currents are as follows. It can be seen from the figure that when Sc is not added in Example 5-6, the alloy lacks the refinement effect of the Al3Sc phase and the more efficient grain boundary strengthening ability, resulting in a weakened overall strengthening effect, and the wear rate is slightly higher than that of the embodiment in which Sc and Zr are added at the same time; while in Comparative Example 6-7, no Sc and Zr are added, and the wear rate is significantly increased.

[0110] The wear rate of Examples 1-6 and Comparative Example 5 tends to be stable under different current conditions of 0-180A. 3 N -1 m -1 range, excellent performance; comprehensive analysis of mechanical properties and current-carrying wear performance under different currents shows that the performance of the aluminum alloys prepared in Examples 1-6 is better than that of the aluminum alloys prepared in Comparative Examples 1-7. The wear performance of the aluminum alloy materials prepared in Examples 1-6 is further analyzed below.

[0111] 2.2 Analysis of current-carrying wear performance of aluminum alloy materials at different sliding speeds

[0112] Figure 5The wear rate change curve of the aluminum alloy prepared in Examples 1-6 at different sliding speeds can be seen from the figure. As far as the overall change trend is concerned, with the increase of sliding speed, the friction coefficient generally shows a trend of gradually decreasing. When the wear temperature is high at 10-30r / s, graphite and Cu transfer and adhere to the alloy surface, and adhesion occurs on the surface. The resistance overcome by friction is large, resulting in a high friction coefficient. With the increase of sliding speed, the reduction of wear temperature weakens the material transfer and softening, the adhesive wear weakens, the resistance of the alloy during tangential rotation decreases, and the friction coefficient decreases accordingly. The friction coefficient of the aluminum alloy material of the present application at different sliding speeds is between 0.03 and 0.08, which helps to achieve lower friction and wear, thereby improving the reliability and service life of the equipment.

[0113] In summary, the aluminum alloy material prepared by the present invention has excellent wear resistance and mechanical strength, and can well meet the performance requirements for preparing current-carrying friction pair materials.

[0114] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.

Claims

1. An aluminum alloy material for a current-carrying friction pair, characterized in that: The invention comprises the following components in weight percentage: 5-10% Cu, 0-0.3% Sc, 0.2-0.6% Zr, and the balance is Al and inevitable impurities.

2. The aluminum alloy material for current-carrying friction pair according to claim 1, characterized in that: The invention comprises the following components in weight percentage: 5-10% Cu, 0.1-0.25% Sc, 0.3-0.5% Zr, and the balance is Al and inevitable impurities.

3. The method for preparing the aluminum alloy material for current-carrying friction pair according to claim 1 or 2, characterized in that: The following steps are involved: S1. Pretreatment: According to the weight percentage of each element in the aluminum alloy material, the raw materials are prepared according to the alloy composition and the amount of burn-off, and the raw materials are pretreated for use; the weight percentage of each element is 5-10% Cu, 0-0.3% Sc, 0.2-0.6% Zr, and the balance is Al and unavoidable impurities; S2. Alloy smelting: heating the aluminum raw material to melt, then adding the Cu raw material, the Sc raw material and the Zr raw material to the molten aluminum liquid, stirring for 10 to 20 minutes, and then passing an inert gas into the molten metal liquid for degassing for 5 to 20 minutes to obtain an alloy melt; S3. Die casting: The alloy melt temperature is adjusted to 620-650°C, poured into a die casting machine for die casting, the mold is preheated in advance, the injection speed is 0.3-0.5 m / s, the injection pressure is 100-120 MPa, and after the injection is completed, the pressure is maintained for 3-10 seconds to obtain a die casting; S4. Heat treatment: The die casting is subjected to solution treatment and aging treatment in sequence, and then air-cooled to room temperature.

4. The method for preparing the aluminum alloy material for current-carrying friction pairs according to claim 3, characterized in that: The pretreatment in step S1 is to remove impurities and oil stains on the surface of the aluminum raw material and the copper raw material and dry them for standby use.

5. The method for preparing the aluminum alloy material for current-carrying friction pairs according to claim 4, characterized in that: The aluminum raw material is pure aluminum, the Cu raw material is T2 copper, the Sc raw material is Al-Sc master alloy, and the Zr raw material is Al-Zr master alloy.

6. The method for preparing the aluminum alloy material for current-carrying friction pairs according to claim 3, characterized in that: The solution treatment parameters are 538℃×21h, and the aging treatment parameters are 175℃×4.5h or 195℃×3h.

7. The method for preparing the aluminum alloy material for current-carrying friction pairs according to claim 3, characterized in that: In step S2, alloy smelting is carried out in an industrial resistance furnace at a heating temperature of 820°C.

8. The method for preparing the aluminum alloy material for current-carrying friction pairs according to claim 3, characterized in that: The inert gas is argon.

9. The method for preparing the aluminum alloy material for current-carrying friction pairs according to claim 3, characterized in that: The mold preheating temperature is 200℃.

10. The method for preparing the aluminum alloy material for current-carrying friction pairs according to claim 3, characterized in that: In step S3, the injection speed in the die-casting is 0.4 m / s, the injection pressure is 106 MPa, and after the injection is completed, the pressure is maintained for 5 seconds.

Citation Information

Cited By

  • Graphene reinforced Al-Cu composite material and preparation method

    CN121344437A